background image

4 Function spaces of posets

Definition 11.

Let

A

i

is a family of posets indexed by some set dom

A

. We will define order of

families of posets by the formula

a

b

⇔ ∀

i

dom

A

:

a

i

b

i

.

I will call this new poset

A

=

Q

A

the function space

of posets and the above order

product order

.

Proposition 12.

The function space for posets is also a poset.

Proof.

Reflexivity.

Obvious.

Antisymmetry.

Obvious.

Transitivity.

Obvious.

Obvious 13.

A

has least element iff each

A

i

has a least element. In this case

Least

(

A

) =

Y

i

dom

A

Least

(

A

i

)

.

Proposition 14.

a

b

⇔ ∃

i

dom

A

:

a

i

b

i

for every

a, b

Q

A

.

Proof.

a

b

⇔ ∃

c

Q

A

: (

c

a

c

b

)

⇔ ∃

c

Q

A

i

dom

A

: (

c

i

a

i

c

i

b

i

)

i

dom

A

x

Q

A

: (

x

a

i

x

b

i

)

⇔ ∀

i

dom

A

:

a

i

b

i

.

Proposition 15.

1. If

A

i

are join-semilattices then

A

is a join-semilattice and

A

B

=

λi

dom

A

:

Ai

Bi.

(2)

2. If

A

i

are meet-semilattices then

A

is a meet-semilattice and

A

B

=

λi

dom

A

:

Ai

Bi.

(3)

Proof.

It is enough to prove the formula (2).

It’s obvious that

λi

dom

A

:

Ai

Bi

A, B

.

Let

C

A, B

. Then (for every

i

dom

A

)

Ci

Ai

and

Ci

B i

. Thus

Ci

Ai

B i

that is

C

λi

dom

A

:

Ai

Bi

.

Corollary 16.

If

A

i

are lattices then

A

is a lattice.

Obvious 17.

If

A

i

are distributive lattices then

A

is a distributive lattice.

Obvious 18.

If

A

i

are (co-)brouwerian lattices then

A

is a (co-)brouwerian lattice.

Proposition 19.

If

A

i

are boolean lattices then

Q

A

is a boolean lattice.

Proof.

We need to prove only that every element

a

Q

A

has a complement. But this complement

is evidently

λi

dom

a

:

a

i

.

Proposition 20.

If

A

i

are lattices then for every

S

P

Q

A

1.

F

S

=

λi

dom

A

:

F

{

x

i

|

x

S

}

whenever

F

{

x

i

|

x

S

}

exists;

2.

d

S

=

λi

dom

A

:

d

{

x

i

|

x

S

}

whenever

d

{

x

i

|

x

S

}

exists.

Proof.

It’s enough to prove the first formula.

(

λi

dom

A

:

F

{

x

i

|

x

S

}

)

i

=

F

{

x

i

|

x

S

} ⊒

x

i

for every

x

S

and

i

dom

A

.

Let

y

x

for every

x

S

. Then

y

i

x

i

for every

i

dom

A

and thus

y

i

F

{

x

i

|

x

S

}

=

(

λi

dom

A

:

F

{

x

i

|

x

S

}

)

i

that is

y

λi

dom

A

:

F

{

x

i

|

x

S

}

.

Thus

F

S

=

λi

dom

A

:

F

{

x

i

|

x

S

}

by the definition of join.

Function spaces of posets

3